Optimizing Salmonella enterica serovar Typhimurium for bacteria-mediated tumor therapy. (3rd March 2016) - Felgner, Sebastian; Kocijancic, Dino; Frahm, Michael; Curtiss, Roy; Erhardt, Marc; Weiss, Siegfried
ABSTARCT: Bacteria-mediated tumor therapy using Salmonella enterica serovar Typhimurium is a therapeutic option with great potential. Numerous studies explored the potential of Salmonella Typhimurium for therapeutic applications, however reconciling safety with vectorial efficacy remains a major issue. Recently we have described a conditionally attenuated Salmonella vector that is based on genetic lipopolysaccharide modification. This vector combines strong attenuation with appropriate anti-tumor properties by targeting various cancerous tissues in vivo . Therefore, it was promoted as an anti-tumor agent. In this addendum, we summarize these findings and demonstrate additional optimization steps that may further improve the therapeutic efficacy of our vector strain.